External validation of the MidiCAT variant of thrombography: Comparison with calibrated automated thrombography and study of the centrifugation scheme - Charles, Sebastien; Guyotat, Denis; Fontana, Pierre; Tardy, Bernard; Lecompte, Thomas; Chalayer, Emilie (Frontiers in Cardiovascular Medicine, 2022)
Introduction To perform Calibrated Automated Thrombography (CAT), the use of reduced plasma volumes (referred to as “MidiCAT”) makes it possible to more efficiently use limited volumes of valuable biobanked plasma samples and decreases expenses for reagents. It is, however, unclear whether the MidiCAT procedure is suitable when thrombin generation (TG) is studied in the presence of added thrombomodulin (TG-TM). Moreover, a simplified centrifugation scheme would facilitate biobanking, if appropriate, for more sensitive coagulation studies. We aimed to compare the results of “MidiCAT” (halved plasma and reagent volumes) with those from regular CAT, in the absence or presence of TM, as well as to study the impact of a single-centrifugation scheme for plasma preparation before freezing. Materials and methods Plasma samples were prepared from the citrated blood from 20 Geneva hospital diverse patients without gross coagulation abnormalities with a single- or double-centrifugation scheme. Samples were kept frozen at −80°C and thawed just before the TG assay in duplicate under two conditions: 1 pM tissue factor (TF) or 5 pM TF + TM. Results and discussion (1) We externally validated “MidiCAT” and also extended the validation to TG-TM. Whatever the method (CAT or MidiCAT), intra-assay (assessed with duplicates) CV was below 6% (1 pM TF) or below 10% (5 pM TF + TM) for ETP. Agreement between the MidiCAT and CAT results was satisfactory; the p coefficients were above 0.95 for ETP and above 0.90 for most other parameters; biases for ETP were +10.0% (1 pM FT) and +13.5% (5 pM + TM). (2) The centrifugation scheme markedly affected the results obtained in the presence of TM, whereas the bias and limit of agreement (difference plots) were low for the no TM condition. The bias in the presence of TM was obvious, more marked with plasma samples sensitive to TM when double centrifuged: the lower the ETP-TM, the greater the relative difference between the ETP-TM of plasma samples prepared with just single centrifugation and the reference plasma samples. Thus, a single-centrifugation procedure, as is often used for plasma biobanking, is suitable for TG study only if it is not performed in the presence of TM.